ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA PENGELOLAAN LIMBAH DI PABRIK GULA ASSEMBAGOES SITUBONDO - Anandatul Firdausia; Abd. Mujib; Setyawardhana Nugraha (Accounting Journal of Ibrahimy (AJI), 2025)
The current rise in environmental issues indirectly requires companies to think about their environment. Environmental accounting reporting is needed to provide relevant information to stakeholders and also increase public trust. In addition to being profit-oriented, companies also need to think about several aspects including social and environmental. This study uses a qualitative methodology with descriptive analysis with the aim of concluding something specific so that it becomes general. Research data was obtained by conducting interviews with 3 employees at PG. Assembagoes Situbondo. The results of this study indicate that the environmental costs incurred by PG. Assembagoes are not in accordance with PSAK No. 1 of 2015 because there is no specific presentation and disclosure of environmental information. Meanwhile, regulations related to waste, namely the regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 56 of 2016 with regulations related to CSR programs, namely the Limited Liability Company Law Article 74 Number 40 of 2007, are in accordance with existing regulations. Environmental accounting and CSR programs that have been implemented by the Assembagoes Sugar Factory support business sustainability by providing positive and negative impacts on the Company.